Knowledge, attitude, and perception of the farmers pepper farming toward sustainability - Tan, Albinus (Human Resource Management Academic Research Society, 2021)
Sustainable Pepper Farming (SPF) can be considered one of the ways to increase the production of pepper in Sarawak by the government. Less or low of attitude, values, and perception on SPF become the problem and slow down the process of extending the idea to the pepper farmers. Even though, this issue needs more attention, but the number of studies is still inadequate. The issue of decreasing or neglecting the pepper farm when the price fluctuates is not a new thing in this industry. Hence, the main aim of this concept paper is to critically review and identify groups in current literature on extension agents’ value, attitude, and perception of the farmers towards sustainable farming, explore the role around them and come out with recommendation for future research. This study will apply a quantitative approach through the questionnaire form for purpose of data collection. A total of 400 respondents from nine branches in Sarawak (Kuching, Serian, Sri Aman, Betong, Sarikei, Bintangor, Sibu, Miri and Bintulu) will be choosing as respondents for this research. Descriptive statistic and multiple regression method via Statistical Package for Social Science (SPSS) version 26 will be using for analysis the data. The findings of this study will be a reference in formulating the new extension strategy or competency to enhance the sustainability of the commodity through Malaysian Pepper Board and Sarawak Agriculture Department. New formulation needed to enhance the extension and to make sure that the farmers will never have abandoned their pepper farm when the price fluctuates. These findings would be helpful in developing an appropriate approach in the technology transfer and farmers training. Future studies are suggested to include more indicators like training to keep the farming sustainability in Sarawak.